STUDY ANALISIS QOS PADA JARINGAN MULTIMEDIA MPLS - M. Yanuar Hariyawan; M. Susantok; Rini Tampubolon (UIN Sultan Syarif Kasim Riau, 2011)
AbstractMulti Protocol Label Switching (MPLS) is one method of tunning network to improve network performance. MPLS technology allows the packets in the system in a shorter time compared with a normal IP network, since the MPLS network for each packet is labeled and then used as information for the switching process replaces the IP header to the routing process. In this paper discussed the convergence of audio and video streaming with MPLS as a backbone network. QoS testing is done using MPLS network testbed, to determine the performance of QoS in MPLS-based video streaming. In the implementation of the system using the testbed network, network performance compared with using MPLS and TCP / IP network. QoS parameters are used to compare the two networks are delay, jitter, packet loss and throughput. With this analysis, expected users of streaming video technology to know the extent to which the performance of such applications through the MPLS network. From the results of research can be concluded that the overall performance of the network that implements MPLS backbone superior to the network without MPLS. Delay and jitter resulting in an MPLS network is smaller than the TCP / IP network with an average difference of delay of 1.46 ms and jitter of 0.02 ms. Necessary speed video and audio packets to a destination using MPLS network is faster than through an IP network for 1.333 ms. In the delivery of video packets that packet loss is obtained through an IP network is greater than the MPLS network. Keywords: MPLS network, TCP/IP Network, Video Streaming, QoS